SOCIO-ECONOMIC PERFORMANCE OF A SOLAR FLAT PLATE COLLECTOR BASED IN A HEAT PUMP WATER HEATING SYSTEM IN THE BRAZILIAN SOUTHEAST - Rodríguez, O. R. S.; Koury, R. N. N.; Maia, A. A. T. (Revista de Engenharia Térmica, 2016)
By increasing renewable energy demand, the use of solar energy has been widely investigated over the recent years. Brazil is a privileged country in terms of the levels of receivable solar radiation in almost all over its territory. However, as there are days when there is a deficit in solar energy, because the day be cloudy or rainy days, and for this reason, solar collectors need a support to contribute to the water heating to the desired temperature. In this work, an experimental study of a heat pump operated with R-134a, as an ancillary equipment for a solar water heating system in Belo Horizonte city has been accomplished. For this project, is used a set of electrical resistances for by a power control step, simulate historical annual values of solar radiation. In the results, it was observed that is achieved through the collection of solar energy the temperature of 45°C in the reservoir only in January, and the other eleven months is necessary to use the heat pump to achieve reach that temperature. With the heat pump operating in conditions similar to real conditions gave an average annual consumption of 137.65 kWh and a cost of R$ 60.61.